2015
DOI: 10.1001/jama.2015.10858
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Is Medicine

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 8 publications
6
73
0
1
Order By: Relevance
“…The dose-response association between physical activity and cardiovascular outcomes is well described (10). As little as 15 min/day of moderate-intensity exercise significantly lowers the risk for cardiovascular morbidity and mortality.…”
mentioning
confidence: 99%
“…The dose-response association between physical activity and cardiovascular outcomes is well described (10). As little as 15 min/day of moderate-intensity exercise significantly lowers the risk for cardiovascular morbidity and mortality.…”
mentioning
confidence: 99%
“…Several recent papers have explored the dose-response relationship between physical activity and adverse health outcomes [31][32][33]. A pooled analysis including 661,137 men and women from 6 large prospective American and European population studies found a 20% risk reduction for all-cause mortality in individuals performing moderate-intensity physical activity <100 min/week during 14 years of follow-up [34].…”
Section: The Optimal Exercise Dosementioning
confidence: 99%
“…It may well be that initial increases in cardiorespiratory fitness decrease the risk for AF, but that excessive exercise training and associated fitness increase the AF risk. Women Study and Copenhagen City Heart study may relate to the characteristics of the most active individuals (high smoking prevalence and low socioeconomic status [31]) and definition of the control group (allowed to exercise <2h/week [58]). Therefore, we believe that there is currently no solid evidence for an increased risk for adverse outcomes in the most active individuals.…”
Section: Too Much Exercise?mentioning
confidence: 99%
“…Higher levels of physical activity are associated with a lower risk of CV events [1,2] and elite athletes live longer than the general population [3]. Nevertheless, there is debate on the dose-response relationship of exercise and CVD outcomes [4,5] and whether high volumes of exercise may accelerate coronary atherosclerosis [6,7].…”
mentioning
confidence: 99%